Pelanggaran Prinsip Kerja Sama dalam Variety Show Jepang Gyouretsu no Dekiru Houritsu Soudanjo - Indrayani, Luh Komang (Humanis; Vol 22 No 4 (2018)DO - 10.24843/JH.2018.v22.i04.p19, 2018)
The research deals with The Violation of Cooperative Principle in Japanese Variety Show Gyouretsu no Dekkiru Houritsu Soudanjo. This research aims to identify types and function of the violation of cooperative principle in Japanese variety show gyouretsu no dekiru houritsu soudanjo. The theory used are cooperation principle (Grice, 1975) and speech acts theory (Searle, 1979). The data are collected using the method of referring by listening to the variety show and transcribing the data. This research is analyzed with padan pragmatic method.To present the result of data analysis using informal method. Based on the analysis, there are 20 forms of violation of cooperative principle. There are 7 data which violated the maxim of quantity, 4 data which violated the maxim of quality, 5 data which violated the maxim of relevance, 4 data which violated the maxim of manner, and 1 data which violated 2 maxim. There are, violated the maxim of quantity and violated the maxim of relevance. The purposes of violating cooperative principle in variety show gyouretsu no dekiru houritsu soudanjo consist 5 illocutionary speech acts. These purposes are 1) assertive: complaining,  informing , lying, and enforcing; 2) directive: consenting, requesting, and ordering; 3) expressive: mocking, arrogant, joking,  teasing, thanking,  pardoning, deploring, ridiculing, and praising; 5) declarative: deciding, to say an opinion, and naming.